Clothing the colony : nineteenth-century Philippine sartorial culture, 1820-1896 - Coo, Stephanie (Quezon City : Ateneo de Manila Press, 2019)
This book is, to date, the most comprehensive and rigorously-researched study on the forms of dress worn by almost all types and classes of inhabitants of the Philippines under Spain from 1820 to 1896. Using an interdisciplinary approach, it systematically and perspicaciously shows the inextricable links between these attires and the rapidly changing economic, political, religious, and social conditions of the nineteenth century, which, among others, witnessed the opening of the islands to international trade, the consequent rise of a mestizo elite, and the formation of groups of Filipinos who would eventually assert their identity through the ideology of reform, and later, revolution at century$1 (Bs end. s
Introduction -- Chapter 1. The Colonial Context -- Chapter 2. The production of clothing -- Chapter 3. Evolution and meaning of lowland, christianized women's clothing -- Chapter 4. Lowland, Christianized men's clothing at a time of waning and emerging powers -- Chapter 5. Balancing pomp and pageantry with modestry and propriety -- Chapter 6. Clothing of Europeans and chinese in the colony -- Conclusion.
Includes bibliographical references and index.
Keywords: CLOTHING AND DRESS -- PHILIPPINES -- HISTORY -- 19TH CENTURY; TEXTILE FABRICS -- PHILIPPINES -- HISTORY; CHRISTIAN WOMEN -- CLOTHING -- PHILIPPINES -- HISTORY